SYNTHESIS, REACTIONS, AND PHARMACOLOGICAL APPLICATIONS OF 2-AMINOBENZIMIDAZOLES: AN UPDATE - Motghare, Apeksha; Katolkar, Parimal (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Many drug molecules comprises of benzo fused heterocycles with two nitrogen atoms, that is, benzimidazole and its derivatives. Many biological active molecules contain that 2-aminobenzimidazole cores are among the foremost common structural components in medicinal chemistry. 2-aminobenzimidazole and its derivative have wide range of biological and pharmaceutical activities. In this review, the authors summarize synthesis, various chemical reactions, and biological activities of 2-aminobenzimidazole and its derivative.